Self?control in adult humans: variation in positive reinforcer amount and delay (1986)
In five experiments, choice responding of female human adults was examined, as a function of variations in reinforcer amount and reinforcer delay. Experiment 1 used a discrete?trials procedure, and Experiments 2, 3, 4, and 5 used a concurrent variable?interval variable?interval schedule. Reinforcer amount and reinforcer delay were varied both separately and together. In contrast to results previously reported with pigeons, the subjects in the present experiments usually chose the larger reinforcers even when those reinforcers were delayed. Together, the results from all the experiments suggest that the subjects followed a maximization strategy in choosing reinforcers. Such behavior makes it easy to observe self?control and difficult to observe impulsiveness in traditional laboratory experiments that use adult human subjects.